How game advertising influences the brand equity of luxury brands - Rodrigues, M.; Romero, M. I.; Loureiro, S. M. C. (2023 Global Marketing Conference at Seoul: Marketing and management transformation in the challenging digital environment, 2023)
Throughout recent years, many physical establishments were forced to close, and events were canceled due to the outbreak of Covid-19. Consequently, brands, especially luxury brands, saw their contact with consumers greatly diminished and revenues decreased significantly (D’Arpizio et al., 2021). On the contrary, the global gaming industry saw its demand, exposure, and revenues increase. In fact, this industry is expected to exceed $200 billion by the end of 2023 (Gilliland, 2020), and there were more than 2.6 billion players worldwide in 2020 (Palframan, 2021). Thus, in 2020, many luxury brands opted to significantly upsurge their investments in the world of online gaming. The adoption of game advertising also represents a way for the luxury industry to adapt to its current target, as 81% of Gen Z and 77% of Millennials are gamers (Jain, 2021). By 2025, both generations are expected to account for 50% of the market, making them important players in the sector. However, there is still little empirical research regarding consumers’ perceptions of game advertising in the context of luxury brands. Thus, this research aims to study the impact that brand credibility and the use of game advertising have on the perceived coolness of luxury brands and, subsequently, on their equity.